1973
DOI: 10.1364/ao.12.001031
|View full text |Cite
|
Sign up to set email alerts
|

Point-Spread Functions, Line-Spread Functions, and Edge-Response Functions Associated with MTFs of the Form exp [−(ω/ωc)n]

Abstract: Point-spread functions, line-spread functions, and edge-response functions associated with modulation transfer functions (MTFs) of the form exp[-(omega/omega(c))(n)] are tabulated for values of the MTF index (n) in the range from n = 1.0 to n = 2.0, in steps of 0.10. The MTFs are also tabulated in this range. Measurements of any one of these four image transfer functions which agree with the tabulated valves for a given set of MTF parameters (omega(c,)n) allow the other three functions to be estimated by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…In the following, an alternative to (9) and (13) is suggested focusing on increasing resolution in intensity profiles while limiting computational effort. The approach is inspired by Verbeek and van Vliet, 18 where the accuracy of higher order derivative based edge detection methodologies is assessed.…”
Section: Geometric Interpretation Of Convolution Principlementioning
confidence: 99%
See 1 more Smart Citation
“…In the following, an alternative to (9) and (13) is suggested focusing on increasing resolution in intensity profiles while limiting computational effort. The approach is inspired by Verbeek and van Vliet, 18 where the accuracy of higher order derivative based edge detection methodologies is assessed.…”
Section: Geometric Interpretation Of Convolution Principlementioning
confidence: 99%
“…[3][4][5] Although the majority of detection algorithms are based on recorded intensity patterns, be it in terms of Hough transforms, 6 intensity gradients 7 or higher order derivatives, 8 so far neither an inherent analytical model of the ellipse image nor an easy way of modelling intensity profiles has to the best of the author's knowledge been presented. While analytical models exist for the straight edge response function 9 involving the error function, an analytical solution is not as straightforward for curved edges.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that MTF's can be fitted to a curve of the form e "'' [18]. For reasonable MTF's the exponent will be a number between 1 and 2.…”
Section: -I-> Nmentioning
confidence: 99%
“…Recall that from (7), the system otf satisfies logĥ(ρ) ∼ (1 − c)p(ρ), ρ ≫ 1, for some unknown positive constant c < 1. Continuation all the way to t = 0 in (22), withĥ(ξ, η, t) as in (23), is equivalent to falsely setting c = 0 in (7). This necessarily produces oversharpening.…”
mentioning
confidence: 99%